Dynamic shock wave driven simultaneous crystallographic and molecular switching between α-Fe2O3 and Fe3O4 nanoparticles – a new finding. Issue 23 (7th June 2022) - Sivakumar, A.; Rita, A.; Sahaya Jude Dhas, S.; Reddy, K. P. J.; Kumar, Raju Suresh; Almansour, Abdulrahman I.; Chakraborty, Shubhadip; Moovendaran, K.; Sridhar, Jayavel; Martin Britto Dhas, S. A.
Abstract : We present the experimentally observed solid-state molecular level switchable phase transitions of nanocrystalline iron oxide materials {α-Fe2 O3 ( R -3 c ) to Fe3 O4 ( Fd -3 m ) and Fe3 O4 ( Fd -3 m ) to α-Fe2 O3 ( R -3 c )} under dynamic shock wave loaded conditions. Abstract : Switchable nanostructured materials with a low-cost and fast processing have diverse practical applications in the modern electronic industries, but such materials are highly scarce. Hence, there is a great demand for identifying the externally stimulated solid-state switchable phase transition materials for several industrial applications. In this paper, we present the experimentally observed solid-state molecular level switchable phase transitions of nanocrystalline iron oxide materials: {α-Fe2 O3 ( R -3 c ) to Fe3 O4 ( F d-3 m ) and Fe3 O4 ( F d-3 m ) to α-Fe2 O3 ( R -3 c )} under dynamic shock wave loaded conditions, and the results were evaluated by diffraction, and vibrational and optical spectroscopic techniques. To date, this is most probably the first report which demonstrates the simultaneous molecular and crystallographic switchable-phase-transitions enforced by dynamic shock waves such that the title material is proposed for sensors and molecular switching applications.